Improving the Performance of Cooperative Platooning with Restricted Message Trigger Thresholds - Vasconcelos Filho, Ênio (2022)
Cooperative Vehicular Platooning (Co-VP) is one of the most prominent and challenging applications of Intelligent Traffic Systems. To support such vehicular communications, the ETSI ITS G5 standard specifies event-based communication profiles, triggered by kinematic parameters such as speed. The standard defines a set of threshold values for such triggers but no careful assessment in realistic platooning scenarios has been done to confirm the suitability of such values. In this work, we investigate the safety and performance limitations of such parameters in a realistic platooning co-simulation environment. We then propose more conservative threshold values, that we formalize as a new profile, and evaluate their impact in the longitudinal and lateral behaviour of a vehicular platoon as it carries out complex driving scenarios. Furthermore, we analyze the overhead introduced in the network by applying the new threshold values. We conclude that a pro-active message transmission scheme leads to improved platoon performance for highway scenarios, notably an increase greater than 40% in the longitudinal performance of the platoon, while not incurring in a significant network overhead. The obtained results also demonstrated an improved platoon performance for semi-urban scenarios, including obstacles and curves, where the heading error decreases in 26%, with slight network overhead.